2019
DOI: 10.21831/jpv.v9i3.26734
|View full text |Cite
|
Sign up to set email alerts
|

The need of practical teaching in vocational high school of Automation and Office Management Program

Abstract: The success of vocational education cannot be separated from the proper management of learning by its objectives.  This study aims to explore the pitfalls and the needs of practical teaching in the Vocational High School of Automation and Office Management Program (AOMP) in Yogyakarta city. This research uses a descriptive method with a qualitative approach. The data obtained were analyzed by using the qualitative analysis model of Miles and Huberman with stages: data reduction, presenting data, verifying data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
1
3
0
3
Order By: Relevance
“…Even though some students felt that the lack of working tools hampered their chance to learn practical skills, others felt that working with friends is much better than working on tools alone. Lack of facilities has also been reported in the previous study on vocational high school by Hermanto et al (2019). Further, Setiawati and Sudira (2015) argued the significance of facilities to motivate students in learning.…”
Section: Laboratory Facilitiessupporting
confidence: 58%
See 1 more Smart Citation
“…Even though some students felt that the lack of working tools hampered their chance to learn practical skills, others felt that working with friends is much better than working on tools alone. Lack of facilities has also been reported in the previous study on vocational high school by Hermanto et al (2019). Further, Setiawati and Sudira (2015) argued the significance of facilities to motivate students in learning.…”
Section: Laboratory Facilitiessupporting
confidence: 58%
“…A low number of students enrolled at the community academy must have something to do with the community perception and motivation to study for higher education. Previous studies have reported how the lack of vocational school's laboratory facilities (Hermanto et al, 2019) has lower student motivation to work well in class (Setiawati & Sudira, 2015). The constraint in community perception and interest continue to prevail, as suggested by Saputri, Artana, and Haris (2013).…”
Section: Introductionmentioning
confidence: 93%
“…Dalam model ini, analisis dilakukan secara interaktif dan terus menerus hingga dirasa cukup yang digambarkan dalam empat langkah. Empat langkah tersebut meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan dan verifikasi (Hermanto, Sutirman, Hidayati, & Sholikah, 2019).…”
Section: Metode Penelitianunclassified
“…Dalam model ini, analisis dilakukan secara interaktif dan terus menerus hingga dirasa cukup yang digambarkan dalam empat langkah. Empat langkah tersebut meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan [13].…”
Section: Metodeunclassified